Factors Influencing The Social-Emotional Development of Children And Adolescents: A Study Systematic Literature Review - Yane Ardian Rachman; Ujang Sumarwan; Melly Latifah; Tin Herawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Adolescence brings about major changes that are intertwined in all domains of development, not only in the physical dimension but also in social-emotional development. This study aims to analyze the factors that influence the social-emotional development of children and adolescents. This study used a systematic literature review method. The analysis used was the Preferred Reporting Item for Systematic Review and Meta-Analytic (PRISMA) method. After scanning titles, abstracts and inclusion criteria, 575 journals were analyzed. Some findings were excluded because they did not meet the criteria, so the number of journals included in the discussion totaled 38 articles. The results showed that factors influencing socio-emotional development were grouped into six factors, namely socio-economic characteristics, mother-child interactions, risky behavior and device use, parental psychological conditions, attachment and parenting, and school learning programs. Suggestions that can be given are improving the psychological well-being of mothers, maintaining and increasing positive interactions between mothers and adolescents, parents have attachment and conduct positive parenting, adolescents have the ability to recognize and manage emotions.